WNT/β-catenin pathway activation in Myc immortalised cerebellar progenitor cells inhibits neuronal differentiation and generates tumours resembling medulloblastoma - Rogers, H.A.; Sousa, S.; Salto, C.; Arenas, E.; Coyle, B.; Grundy, Richard G. (Cancer Research UK, 2012)
Background: Medulloblastoma is the most common malignant childhood brain tumour. Aberrant activation of the WNT/β-catenin pathway occurs in approximately 25% of medulloblastomas. However, its role in medulloblastoma pathogenesis is not understood. Methods: We have developed a model of WNT/β-catenin pathway-activated medulloblastoma. Pathway activation was induced in a Myc immortalised cerebellar progenitor cell line through stable expression of Wnt1. In vitro and in vivo analysis was undertaken to understand the effect of pathway activation and identify the potential cell of origin. Results: Tumours that histologically resembled classical medulloblastoma formed in vivo using cells overexpressing Wnt1, but not with the control cell line. Wnt1 overexpression inhibited neuronal differentiation in vitro, suggesting WNT/β-catenin pathway activation prevents cells terminally differentiating, maintaining them in a more ‘stem-like’ state. Analysis of cerebellar progenitor cell markers demonstrated the cell line resembled cells from the cerebellar ventricular zone. conclusion: We have developed a cell line with the means of orthotopically modelling WNT/β-catenin pathway-activated medulloblastoma. We provide evidence of the role pathway activation is playing in tumour pathogenesis and suggest medulloblastomas can arise from cells other than granule cell progenitors. This cell line is a valuable resource to further understand the role of pathway activation in tumorigenesis and for investigation of targeted therapies.